Stronger wind, smaller tree: Testing tree growth plasticity through a modeling approach - Wang, Haoyu; Hua, Jing; Kang, Mengzhen; Wang, Xiujuan; Fan, Xing-Rong; Fourcaud, Thierry; de Reffye, Philippe (Frontiers in Plant Science, 2022)
Plants exhibit plasticity in response to various external conditions, characterized by changes in physiological and morphological features. Although being non-negligible, compared to other environmental factors, the effect of wind on plant growth is less extensively studied, either experimentally or computationally. This study aims to propose a modelling approach that can simulate the impact of wind on plant growth, to add this factor into the digital world of plants. Tree reaction to the wind is simulated based on the hypothesis that plants tend to fit best the environment. This is interpreted as an optimization problem of finding the best growth-regulation sink parameters giving the maximal plant fitness (usually seed weight, but expressed as plant size). To test this hypothesis in silicon, a functional-structural plant model (FSPM), which simulates both the primary and secondary growth of stems, is coupled with a biomechanical model which computes forces, moments of forces and breakage location in the stems caused by both wind and self-weight increment during plant growth. Nondominated Sorting Genetic Algorithm II (NSGA-II) is adopted to maximize the multi-objective function (stem biomass and tree height) by determining a key parameter value controlling the biomass allocation to the secondary growth. The digital tree shows considerable phenotypic plasticity under different wind speeds, whose behavior, as emergent properties, is in accordance with experimental results from works of literature: the height and leaf area of individual trees decrease with wind speed, and the diameter at the breast height (DBH) increased at low-speed wind but declined at higher speed wind. Stronger wind results in a smaller tree. The response of trees to the wind is realistically simulated, giving a deeper understanding of tree behavior. The result shows that the challenging task of modelling plant plasticity may be solved by optimizing the plant fitness function. Adding a biomechanical model provides a non-negligible factor in the digital force environment for plants in silicon, opening a wider application of plant models.